Peran Penyuluh Pertanian dalam Pengembangan Kelompok Tani di Kelurahan Matabubu Kecamatan Poasia Kota Kendari - Aslamia, Aslamia; Mardin, Mardin; Hamzah, Awaluddin (Jurnal Ilmiah Membangun Desa dan Pertanian, 2017)
The purpose of this study is to know the role of agriculture counseling in increasing farm group of Kaseiseha in Matabubu Village Poasia Sub-District Kendari Town. This study was on December 2016 in Matabubu Village Poasia Sub-District Kendari Town. The population in this study was all members of Kaseiseha Farm Group in Matabubu Village Poasia Sub-District Kendari Town. The sampling was done by using census method by taking all populations of study as a sample with the number 20 people and using qualitative descriptive analyze which formulating how the role of agriculture counseling in increasing farm group of Kaseiseha in Matabubu Village Poasia Sub-District Kendari Town. The variable was observed the role of agriculture counseling which covers (counselor as the facilitator, as a technician, as an organizer, and as the agent of reformer), increasing of farm group consist of (study tool, corporate mode, and unit of production). The result of the study showed that the role of agriculture counseling in increasing farm group of Kaseiseha, a counselor had been as a facilitator, technician, organizer, but the counselor still less in having a role as an agent of the reformer, while in increasing of farm group, the counselor had been had a role well. This thing can saw in increasing of farm group of Kaseiseha use their farm group as a study tool, corporate mode, and unit of production by guiding of agriculture counselor.